Childlessness and Attitudes Towards Caring for Elderly Parents in Lithuania - Stumbrys, Daumantas; Rapolienė, Gražina; Gedvilaitė-Kordušienė, Margarita; Tretjakova, Vaida (Socialinė teorija, empirija, politika ir praktika, 2024)
In rapidly ageing societies, caring and responsibilities for parents in old age is a widely discussed topic. This is particularly relevant in societies with low fertility and high rates of childlessness. Lithuania is one of the countries where demographic ageing rates have risen sharply in a short period of time. This process has been driven not only by low fertility but also by emigration of middle-aged and young people and increasing life expectancy. There is no lack of research on demographic changes in ageing societies in the country, but very little is known about the attitudes of childless men and women towards caring for their parents in old age. The aim of the study is to determine the attitudes of childless and child-bearing individuals towards parental responsibilities in Lithuania. Our analysis is based on the 2018-2019 ‘Families and Inequality Survey’ dataset collected in Lithuania. The data covers 3,005 individuals aged 34-48 at the time of the survey. The representative sample was obtained by using a stratified sampling method. Face-to-face interviews were carried out with respondents in their homes by using a standardized questionnaire. The data were analysed using descriptive statistics and chi-square methods. We found that the proportion of men (12.0%) who do not want to have children is statistically significantly higher (p=0.003) than the proportion of women (7.6%). We found that childless people were less likely than those with children to agree with the statement that children should look after their parents. In addition, women were more likely than men to agree with these statements. Our findings are important from a practical point of view – when considering social care and pronatalist policy measures. Research project is financially supported by the Research Council of Lithuania (LMTLT), agreement No. P-MIP-22-24.